Beyond Human Teachers: Post-Humanist Perspectives on AI, Cultural Inequities, and Educational Transformation - Ahmed, Sadia (Journal of Posthumanism, 2024)
The swift integration of AI (Artificial Intelligence) in education is redefining learning experiences globally, yet it also exposes and potentially deepens cultural and infrastructural divides between developed and developing nations. Adopting a cultural science framework, this paper presents a comparative analysis of AI adoption in education between Australia and Pakistan, examining five key dimensions, including internet accessibility and bandwidth infrastructure, availability and local relevance of AI-driven learning platforms, educator preparedness and professional development, socio-cultural perceptions of AI in the classroom, and policy frameworks and institutional support for digital transformation. In the context of Cultural Studies and Posthumanism, the integration of AI in education further challenges traditional notions of human agency, identity, and power, reshaping how knowledge is produced and consumed across diverse cultural landscapes (Sain & Thelma, 2023). The literature review reveals that while Australia benefits from a robust digital ecosystem and forward-looking education policies, Pakistan faces systemic challenges, including limited rural connectivity, a lack of teacher training, and minimal investment in localized digital content. These inequalities are not exclusively technology-based but intensely cultural, formed by national priorities, belief in digital systems, and historical inequities in education distribution. This transformation offers complicated reflection on moral and socio-economic structures, mainly in terms of digital transformations, media approaches, and human–non-human connections, which further have a great contribution to interdisciplinary dialogues on the role of Artificial Intelligence in redefining educational experiences based on a cultural and post-humanist lens (Jiang & Shao, 2024). Recommendations emphasize the need for culturally responsive AI education policies, international cooperation to reduce the digital divide, and targeted capacity-building initiatives, especially in teacher training and localized content development. Ultimately, the paper advocates for inclusive AI strategies that respect cultural contexts while promoting equitable access to future-ready education.